Un fantôme dans la machine. Esprit de corps et survie de l’État chez Bourdieu et Deleuze-Guattari - Céline Hervet (Astérion)
Transposing the thorny issue of the union of body and mind onto the political plane, this article investigates what produces the cohesion of the body politic through an inquiry into the genesis and survival of the institution of the State in light of the concept of esprit de corps. While Bourdieu draws on the work of Kantorowicz to consider the genesis of the modern State through the gradual secularisation of the idea of the sovereign’s embodiment of the collective body in the form of unfailing adherence to the incorporated collective body, manifested in the indefectible bond that unites the members of the senior branch of the civil service, beyond time and death. Deleuze and Guattari, in their heterogenesis of the State, draw on Ibn Khaldûn, who sees the esprit de corps as the driving force behind the history of states, both in terms of their growth and decline. The cross-reading of these two works highlights to light the ambivalence of the esprit de corps, the leaven of union and cohesion of the body politic necessary to the birth and survival of the State, which can undermine it by its very nature. Either this bond that unites individuals is weakened within civil society as contractual relations supplant affective ties or, by encouraging the autonomy of specific groups within the state apparatus and society itself, it haunts the state machine like a ghost, ultimately threatening its unity and the preservation of the general interest of which it is the guarantor.